A First Course in Probability and Statistics with Applications - Strait, Peggy Tang. (New York : Harcourt Brace Jovanovich, 1983)
Probability and Statistics with Integrated Software Routines" is a calculus-based treatment of probability concurrent with and integrated with statistics through interactive, tailored software applications designed to enhance the phenomena of probability and statistics. The software programs make the book unique. The book comes with a CD containing the interactive software leading to the Statistical Genie. The student can issue commands repeatedly while making parameter changes to observe the effects. Computer programming is an excellent skill for problem solvers, involving design, prototyping, data gathering, testing, redesign, validating, etc, all wrapped up in the scientific method. It incorporates more than 1,000 engaging problems with answers. It includes more than 300 solved examples, and uses varied problem solving methods.
Includes bibliographies and index.
aia 29/9/17
Loans
Keywords: Probabilities; Mathematical Statistics